Analysis of work motivation of Generation Z in China: an empirical study and implications. - Yu, Xinkai (2022)
This dissertation aims to investigate the work motivation of Chinese Generation Z, by analysing the relationship between need satisfaction and work motivation as well as between work motivation and four work-related outcomes (i.e., work performance, vitality, turnover intention, and absenteeism). The theoretical basis of this dissertation contains Self-Determination Theory and the theory of generation. Following the completion of a pilot study, this research conducted a questionnaire survey obtaining over 200 Chinese Generation Z respondents. Then this study tests the research hypotheses based on descriptive statistics, correlation analysis, and regression analysis. The main findings are that (1) external regulation-material and identified regulation have a greater impact on Generation Z than other types of work motivation; (2) need satisfaction is related to work motivation; (3) work motivation affects work-related outcomes. In conclusion, as for the Chinese Generation Z workers, compared with controlled motivation, the autonomous motivation tends to bring better work-related outcomes. It is therefore recommended that organisational managers should not only considers the controlled motivation, but also pay closer attention to autonomous motivation in the employee management.